ASSOCIATION OF PPARΑ INTRON 7 G/C (RS4253778) POLYMORPHISMS WITH MUSCULAR ENDURANCE AMONG SOCCER SCHOOL STUDENTS IN MEDAN - Roy Wilson Sihaloho; Yahwardiah Siregar; Maya Savira (Universitas Muhammadiyah Sumatera Utara, 2019)
Peroxisome proliferator-activated receptor alpha (PPARα) is the transcription factor gene that regulates lipid metabolism and glucose homeostasis of energy within the mitochondria. PPARα gene Intron 7 variation is associated with the phenotype of human performance. Homozygous GG is more often found among athletes concerning muscular endurance. This study aims to investigate the association of PPARα polymorphism with muscular endurance. Samples from buccal cells were collected from 77 boys (aged 11-16 years). PPARα Intron 7 polymorphism was examined using PCR-RFLP with restriction enzyme TaqI. Meanwhile, the Curl-Up test has been performed to determine the muscular endurance of the subjects. The relationship between PPARα Intron 7 polymorphism with muscular endurance was assessed by using Fisher’s Exact test. The study found the genotype GG and GC of 97.4% and 2.6%, respectively. Muscular endurance was shown among categories of poor (66.2%) and fair (15.6%). Statistical analysis established no association between PPARα polymorphism with muscular endurance (p = 0,564). Keywords: PPARα polymorphisms, muscular endurance, Curl-Up test